The Evolution Of Constitutional Theory: A Historical Study And Its Relevance In Indonesia - Edina, Sheilla Ariestia; Rosidin, Didin Nurul; Toheri, Toheri (Ann Publisher, 2024)
This article discusses the challenges and opportunities in adapting constitutional theory in the context of Indonesia's law and government. It was found that the main challenges include widespread corruption, political instability, plurality and multiculturalism, inconsistencies between national and local laws, and suboptimal enforcement of human rights. On the other hand, there are significant opportunities to overcome these challenges, such as through constitutional reform, the important role of the Constitutional Court, increasing legal education and awareness, the use of information technology for transparency, and international cooperation. This article emphasizes the importance of taking advantage of these opportunities and addressing existing challenges to develop a stronger, fairer, and more democratic constitutional system in Indonesia. Thus, the adaptation of constitutional theory can run more effectively and in accordance with the needs and aspirations of the people of Indonesia.